Application of pipe temperature simulator for Norman Wells oil pipeline - Nixon, JF (Derick); MacInnes, Kaye L (Canadian Geotechnical Journal, 1996)
The Norman Wells oil pipeline has been operating successfully for 10 years, transporting crude oil from the Norman Wells field in the Northwest Territories to southern markets. The temparatures of the oil in the pipeline have been closely monitored at several locations, and a detailed record of the thermal performance of the pipeline and the response of the surrounding permafrost soils is available. Recently, a geothermal program has been developed to predict the temparature profiles along a buried pipeline in more detail than has hitherto been attempted. The recently developed simulator accounts for freezing and thawing around the pipeline, while accounting for the heat losses from the pipeline to the ground as the contents flow through the line. The Norman Wells oil pipeline has provided an opportunity to test and calibrate the new model. Comparaisons between observed temperatures along the line and predictions from the simulator have been made, and the agreement is generally extremely good. The downstream effects of recent changes to the operating temperatures at Norman Wells were accurately predicted, illustrating the potential applications of model. The simulator will allow the effects of future planned changes in operating conditions to be more accurately evaluated, as well as playing an important part in design engineering studies for future oil, water, and gas pipeline projects elsewhere. Key words: pipeline, geothermal, oil temperatures. permafrost, thaw, Norman Wells.